2018
DOI: 10.1108/dlo-03-2017-0027
|View full text |Cite
|
Sign up to set email alerts
|

Improving resilience in high-risk organizations: principles for the design of innovative training situations

Abstract: Purpose Safety and organizational research indicates that fostering resilience in organizations is a promising way for improving safety, albeit concrete means to implement resilience are still lacking, especially in the educational field. The purpose of this paper is to propose four principles for training design derived from past and current studies the authors conduct in high-risk organizations. Design/methodology/approach Training for resilience is considered within an enactive approach of human activity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 4 publications
(6 reference statements)
1
14
0
6
Order By: Relevance
“…In any event, it can be said that strategic practices of human resource, increase the organization's ability to develop new solutions to its problems (McIver et al 2018). A study by Blanco (2018) found that staff training has a positive impact on organizational resilience, especially innovative training (Flandin et al 2018). The role of practices involving the employee in a variety of work functions is not forgotten particularly the impact of these practices in the improved level of organizational resilience (Lengnick-Hall et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In any event, it can be said that strategic practices of human resource, increase the organization's ability to develop new solutions to its problems (McIver et al 2018). A study by Blanco (2018) found that staff training has a positive impact on organizational resilience, especially innovative training (Flandin et al 2018). The role of practices involving the employee in a variety of work functions is not forgotten particularly the impact of these practices in the improved level of organizational resilience (Lengnick-Hall et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of high-performance human resources management practices as described by Kooij and Boon (2018), which were training and development as well as work assignments, the results of Blanco (2018) confirmed that training of all kinds is an important element in improving organizational resilience. Flandin et al (2018) also noted that innovative training is an important element in improving individual and group resilience in organizations. Siddiqui (2017) found that training is a critical element for organizational resilience.…”
Section: Relationship Between Shrm and Organizational Resiliencementioning
confidence: 99%
“…Lorsqu'elle est basée sur un principe de perturbation (Flandin, Poizat, & Durand, 2018), la formation vise à perturber le couplage acteur-environnement des formés. À travers l'activité en formation, c'est l'activité cible qui est visée (le travail, dans le cas d'une formation professionnelle) : on espère donc que la perturbation (i) s'accompagne d'un écho « retentissant » dans le travail, et (ii) touche un niveau structuré, « sédimenté » d'activité que l'on peut qualifier de culture (entendue à la suite de Geertz (1973) comme réseaux de significations que les hommes créent et dont ils dépendent eux-mêmes).…”
Section: Principe De Perturbation En Formationunclassified
“…[58], the authors present a program for training for operational resilience capabilities, emphasizing that training elements should be aimed at sensemaking. Flandin et al [59] argue the design of innovative training situations that are likely to improve individual, collective, and organizational resilience should support participatory-sensemaking and collective sensemaking.…”
Section: Sensemaking As a Factormentioning
confidence: 99%
“…Several of the remaining publications in this review discuss training that is aimed at enhancing resilience [40,48,57,59,64], which is an important feature in dealing with safety-critical situations.…”
Section: Aspects Of Trainingmentioning
confidence: 99%